ChatGPT as Digital Scaffolding in Argumentative Writing for First-Year Students: A Systematic Literature Review (2020–2025) - Dadan Djuanda; Riana Irawati; Diah Gusrayani; Nurdinah Hanifah; Rana Gustian Nugraha; Sidqia Nurfadilah; Regina Lichteria Panjaitan; Enjang Yusup Ali (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
This study examines the use of ChatGPT as a form of digital scaffolding in teaching argumentative writing for first-year college students. Although prior studies highlight the benefits of AI-assisted writing tools, there is still a lack of critical synthesis on how ChatGPT functions across cognitive, metacognitive, and pedagogical dimensions, as well as the risks associated with its use. Addressing this gap, this study employs a Systematic Literature Review (SLR) following PRISMA guidelines, analyzing 40 selected articles (2020–2025) from major academic databases. The findings show that ChatGPT serves as both a writing assistant and an interactive dialogue partner, providing multidimensional scaffolding that enhances idea organization, argument clarity, coherence, and students’ writing confidence. However, this study also identifies key challenges often underexplored in the literature, including over-reliance, academic integrity concerns, and limitations in verifying AI-generated content. These findings contribute a more critical perspective by emphasizing that while ChatGPT has strong potential to support adaptive and interactive learning, its integration must be accompanied by structured pedagogical strategies, strengthened digital and AI literacy, and the promotion of students’ critical thinking to ensure meaningful and independent learning outcomes.